Visual assessment of equirectangular images for virtual reality applications In Unity - Gil, Adriano; Khurshid, Aasim; Postal, Juliana; Figueira, Thiago (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais Estendidos da XXXII Conference on Graphics, Patterns and Images, 2019)
Virtual Reality (VR) applications provide an immersive experience when using panoramic images that contain a 360-degree view of the scene. Currently, the equirectangular image format is the widely used pattern to represent these panoramic images. The development of a virtual reality viewer of panoramic images should consider several parameters that define the quality of the rendered image. Such parameters include resolution configurations, texture-to-objects mappings and deciding from different rendering approach, but to select the optimal value of these parameters, visual quality analysis is required. In this work, we propose a tool integrated within Unity editor to automate this quality assessment using different settings for the visualization of equirectangular images. We compare the texture mapping of a skybox with a procedural sphere and a cubemap using full-reference objective metrics for Image Quality Analysis (IQA). Based on the assessment results, the tool decides how the final image will be rendered at the target device to produce a visually pleasing and high-quality image.